Self-Medication Practices and Associated Factors in the Prevention and/or Treatment of COVID-19 Virus: A Population-Based Survey in Nigeria - Wegbom, Anthony Ike; Edet, Clement Kevin; Raimi, Olatunde; Fagbamigbe, Adeniyi Francis; Kiri, Victor Alangibi (Frontiers in Public Health, 2021)
Background: The anxiety caused by the emergence of the novel coronavirus disease (COVID-19) globally has made many Nigerians resort to self-medication for purported protection against the disease, amid fear of contracting it from health workers and hospital environments. Therefore, this study aimed to estimate the knowledge level, causes, prevalence, and determinants of self-medication practices for the prevention and/or treatment of COVID-19 in Nigeria. Methods: A web-based cross-sectional survey was conducted between June and July 2020 among the Nigerian population, using a self-reported questionnaire. Statistical analysis of descriptive, bivariate, and multivariate analyses was done using STATA 15. Results: A total of 461 respondents participated in the survey. Almost all the respondents had sufficient knowledge about self-medication (96.7%). The overall prevalence of self-medication for the prevention and treatment of COVID-19 was 41%. The contributing factors were fear of stigmatization or discrimination (79.5%), fear of being quarantine (77.3%), and fear of infection or contact with a suspected person (76.3%). The proximal reasons for self-medication were emergency illness (49.1%), delays in receiving hospital services (28.1%), distance to the health facility (23%), and proximity of the pharmacy (21%). The most commonly used drugs for self-medication were vitamin C and multivitamin (51.8%) and antimalarials (24.9%). These drugs were bought mainly from pharmacies (73.9%). From the multivariable logistic regression model, males (OR: 0.79; 95% CI: 0.07–0.54), and sufficient knowledge on SM (OR: 0.64; 95% CI: 0.19–0.77) were significantly associated with self-medication. Conclusion: The key finding of this study was the use of different over-the-counter medications for the prevention (mainly vitamin C and multivitamins) and treatment (antibiotics/antimicrobial) of perceived COVID-19 infection by Nigerians with mainly tertiary education. This is despite their high knowledge and risk associated with self-medication. We suggest that medication outlets, media and community should be engaged to support the rational use of medication.